Development and Application of Artificial Intelligence in Auxiliary TCM Diagnosis. (6th March 2021) - Feng, Chuwen; Shao, Yuming; Wang, Bing; Qu, Yuanyuan; Wang, Qingyong; Li, Yang; Yang, Tiansong
Abstract : As an emerging comprehensive discipline, artificial intelligence (AI) has been widely applied in various fields, including traditional Chinese medicine (TCM), a treasure of the Chinese nation. Realizing the organic combination of AI and TCM can promote the inheritance and development of TCM. The paper summarizes the development and application of AI in auxiliary TCM diagnosis, analyzes the bottleneck of artificial intelligence in the field of auxiliary TCM diagnosis at present, and proposes a possible future direction of its development.